Dictionary of Bisayan arts : Cebuano-Hiligaynon-Waray - Kintanar-Alburo, Erlinda. 4 0 16; 5 (Manila : National Commission for Culture and the Arts, 2009)
Collection of indigenous terms in three Bisayan languages.
Includes bibliographical references.
English, Cebuano, Hiligaynon and Waray.
Keywords: 2 -- 0; 6; Polyglot.;English.;English.;English. -- Arts;Cebuano language;Hiligaynon language;Waray language -- Philippines;Visayan Islands -- 20 -- Dictionaries;Dictionaries;Dictionaries;Dictionaries; 20; 2